Zone-specific Gene Expression Patterns in Articular Cartilage - Grogan, Shawn P. (2013)
OBJECTIVE: Identify novel genes and pathways specific to superficial (SZ), middle (MZ) and deep zones (DZ) of normal articular cartilage. METHODS: Articular cartilage was obtained from knees of 4 normal human donors. The cartilage zones were dissected on a microtome. RNA was analyzed on human genome arrays. Data obtained with human tissue were compared to bovine cartilage zone specific DNA arrays. Genes differentially expressed between zones were evaluated using direct annotation for structural or functional features, and by enrichment analysis for integrated pathways or functions. RESULTS: The greatest differences were observed between SZ and DZ in both human and bovine cartilage. The MZ was transitional between the SZ and DZ and thereby shared some of the same pathways as well as structural/functional features of the adjacent zones. Cellular functions and biological processes enriched in the SZ relative to the DZ, include most prominently ECM receptor interactions, cell adhesion molecules, regulation of actin cytoskeleton, ribosome-related functions and signaling aspects such as Interferon gamma, IL4, CDC42Rac and Jak-Stat. Two pathways were enriched in the DZ relative to the SZ, including PPARG and EGFR/SMRTE. CONCLUSION: These differences in cartilage zonal gene expression identify new markers and pathways that govern the unique differentiation status of chondrocyte subpopulations.